2019
DOI: 10.1186/s13104-019-4170-y
|View full text |Cite
|
Sign up to set email alerts
|

Coaches’ perceptions on qualities defining good adolescent rugby players and are important for player recruitment in talent identification programs: the SCRuM project

Abstract: ObjectiveCompetitive rugby is increasingly becoming popular among adolescent players even in countries hardly known for rugby such as Zimbabwe. Given the increased participation rates, burgeoning talent identification (TID) programs and the reportedly high injury-risk associated with competitive youth rugby, the minimal qualities or skills needed for effective performance by all young players need further clarification. Therefore, this qualitative study was conducted to explore the perceptions of high-school b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Given the complexity and multifaceted nature of the sport of rugby, only examining the anthropometric, physiological and game specific skills is a possible limitation and a more holistic protocol including tactical, perceptual-cognitive skills and psychological measures would have been ideal to comprehensively understand and identify qualities or skills discriminating players of different ages and playing standards [37]. A recent study showed that psychological attributes such as players' attitudes and personality traits, mental strength and emotional stability are key qualities that coaches consider in good adolescent rugby players and in player recruitment for TID initiatives [54]. Further studies objectively assessing these qualities and how they differ with age and playing standards in junior rugby are warranted.…”
Section: Critical Assessment Of the Studymentioning
confidence: 99%
“…Given the complexity and multifaceted nature of the sport of rugby, only examining the anthropometric, physiological and game specific skills is a possible limitation and a more holistic protocol including tactical, perceptual-cognitive skills and psychological measures would have been ideal to comprehensively understand and identify qualities or skills discriminating players of different ages and playing standards [37]. A recent study showed that psychological attributes such as players' attitudes and personality traits, mental strength and emotional stability are key qualities that coaches consider in good adolescent rugby players and in player recruitment for TID initiatives [54]. Further studies objectively assessing these qualities and how they differ with age and playing standards in junior rugby are warranted.…”
Section: Critical Assessment Of the Studymentioning
confidence: 99%
“…This study formed part of the School Clinical Rugby Measure (SCRuM) project described elsewhere [11, 12, 18] and was conducted in two sequential parts. Adopting a pragmatic “in-season” approach previously used by Enright et al [19], the preliminary study established the absolute and relative reliability of each test item in the assembled SCRuM test battery.…”
Section: Main Textmentioning
confidence: 99%
“…Moreover, the reported high physical and technical demands of adolescent RU [1, 5] require junior players to have optimal qualities or technical proficiencies for effective participation. Therefore, research defining key attributes important in competitive schoolboy RU is warranted especially in Zimbabwe where schoolboy RU is emerging and played at different competitive levels [11, 12]. Such evidence has implications on talent identification (TID) and long-term player development [13].…”
Section: Introductionmentioning
confidence: 99%
“…Forty-three studies reported on coaches' training knowledge. 18,29,31,36,37,40,[42][43][44][48][49][50][51][52][53][54][55][56][57][58][61][62][63][64][66][67][68][69][70]73,74,76,80,81,[85][86][87]89,90,92,93,128,131 Eight of these studies were based on rugby league. 43,56,62,64,[66][67][68]81 Coaches agreed that monitoring players are important for training.…”
Section: Thematic Analysismentioning
confidence: 99%